Pemodelan Perlindungan HKI Komunal Warisan Kuliner Tradisional melalui Pendekatan Pluralisme Hukum di Indonesia - Prayitno, Farrel Izham; Abroor Zuhri, A. Nawfal; Tobroni, Faiq; Multazam, Ahmad (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
Traditional culinary knowledge in Indonesia often exists in a legal grey area, particularly when communal cultural expressions are assessed through intellectual property regimes designed for individual ownership. This article focuses on the case of Rendang Minangkabau and examines how its protection can be strengthened within a communal intellectual property rights framework grounded in legal pluralism. Rather than relying solely on doctrinal analysis, this study adopts a simulation-based normative–empirical approach to explore how different regulatory configurations may influence protection outcomes. Four policy scenarios were constructed over a five- year projection period (2024–2028), drawing on secondary data and structured parameter modeling. The analysis incorporates regulatory strength, recognition of adat norms, and benefit- sharing mechanisms as core variables to assess changes in an Effective Protection Index. The findings suggest that legal reform alone is insufficient when detached from customary legitimacy. Scenarios that formally recognize adat institutions and incorporate equitable benefit-sharing mechanisms produce substantially higher protection outcomes compared to the current regulatory configuration. In particular, the recognition of customary norms emerges as the most influential factor in strengthening protection effectiveness. By translating the concept of legal pluralism into an operational policy model, this study moves beyond purely qualitative debates and offers a structured framework for evaluating communal intellectual property protection.